Study on antioxidant activities of the aerial partsand some compounds isolated from Archidendron clypearia ((Jack) I. Niels Part 2. Isolating, determining structure and antioxidant capability of some compounds from ethyl acetate and chloroform extract - Hieu, Le Trung; Huong, Vo Thi Mai; Hoai, Nguyen Thi; Thi, Tran Thi Van (Vietnam Journal of Science and Technology, 2016)
The antioxidant activity in vitro of methanol extract of Archidendron clypearia was evaluated by in vitro tests on isolated liver cells of mouses with ED50 value ​​ of 2.18 μg/mL compared to that of curcumin of 1.87 µg/mL. Using combined chromatographic methods, four compounds were isolated from chloroform extract of the Archidendron clypearia. Their structures were elucidated to be daucosterol, 1-octacosanol, docosenoic acid, and methyl gallate by 1D- and 2D-NMR spectroscopic methods and in comparison with those reported in the literature. This is the first report of these compounds from the plant. All four compounds showed quite high antioxidant activity, for which methyl gallate was the highest one.